1978
DOI: 10.1073/pnas.75.10.5039
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum and autophagy in rat hepatocytes.

Abstract: Electron microscopy of hepatocytes in both normal rat liver and rat liver treated to induce hyperplasia of smooth endoplasmic reticulum shows that autophagic vacuoles and residual bodies (types of lysosomes) are continuous with endoplasmic reticulum. Our laboratory has emphasized the diverse activities of GERL (1, 2) and other regions of the endoplasmic reticulum (ER) in hepatocytes (ref. 3; A. B. Novikoff, P. M. Leuenberger, P. M. Novikoff, and M. Quintana, unpublished results). In 1964 we suggested that in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
1

Year Published

1980
1980
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 8 publications
1
39
0
1
Order By: Relevance
“…The source of the AV membranes in mammalian cells is controversial: some studies (Dunn, Jr, 1990;Ericsson, 1969;Novikoff and Shin, 1978;Ueda et al, 1991) have identified endoplasmic reticulum (ER) proteins on the AVi, others detected Golgi membrane proteins (Locke and Sykes, 1975;Yamamoto et al, 1990). The unusual morphological properties of AVs has also led to the hypothesis that these membranes are derived from a unique type of membrane, called a phagophore (Seglen et al, 1990), or isolation membrane ).…”
Section: Introductionmentioning
confidence: 99%
“…The source of the AV membranes in mammalian cells is controversial: some studies (Dunn, Jr, 1990;Ericsson, 1969;Novikoff and Shin, 1978;Ueda et al, 1991) have identified endoplasmic reticulum (ER) proteins on the AVi, others detected Golgi membrane proteins (Locke and Sykes, 1975;Yamamoto et al, 1990). The unusual morphological properties of AVs has also led to the hypothesis that these membranes are derived from a unique type of membrane, called a phagophore (Seglen et al, 1990), or isolation membrane ).…”
Section: Introductionmentioning
confidence: 99%
“…The origin of the segregating membrane of autophagic vacuoles is still a matter of debate in various cells. In hepatocytes, the majority of reports favors the membranes of ER and Golgi apparatus as the original membrane of autophagic vacuoles from the evidence such as occasional direct continuity of ER membranes with the outer limiting membrane of autophagic vacuoles (14) and the osmium-staining common property of the autophagic vacuole membrane with ER and Golgi apparatus membranes (9). In contradicton, it has been recently reported that the limiting membranes of autophagic vacuoles possess characteristics distinct from the ER and Golgi membranes with respect to the density of intramembranous particles (8,19) and the concentration of cholesterol and unsaturated fatty acids (18).…”
mentioning
confidence: 99%
“…Récemment, le rôle dans la première étape de la formation de l'autophagosome d'une structure membranaire, baptisée omégasome, issue de la membrane du réticulum endoplasmique, a été élégamment montré [21]. Finalement, il n'y pas que le Fou d'Elsa qui réinvente le passé pour voir la beauté de l'avenir puisque dès 1964 le microscopiste américain Alex Novikoff suggérait le rôle primordial du réticulum endoplasmique dans l'initiation de l'autophagie [22]. ‡ Autophagy: time to degrade to go on living P. Codogno Inserm U756, Université Paris-Sud 11 5, rue Jean Baptiste Clément 92296 Châtenay-Malabry Cedex, France.…”
Section: éDitorialunclassified